Surface acoustic waves induced micropatterning of cells in gelatin methacryloyl (GelMA) hydrogels - Naseer, Shahid M.; Walch, Philipp (Biofabrication, 2017)
Acoustic force patterning is an emerging technology that provides a platform to control the spatial location of cells in a rapid, accurate, yet contactless manner. However, very few studies have been reported on the usage of acoustic force patterning for the rapid arrangement of biological objects, such as cells, in a three-dimensional (3D) environment. In this study, we report on a bio-acoustic force patterning technique, which uses surface acoustic waves (SAWs) for the rapid arrangement of cells within an extracellular matrix-based hydrogel such as gelatin methacryloyl (GelMA).
Gesehen am 20.09.2018